2012
DOI: 10.1590/s0104-11692012000500007
|View full text |Cite
|
Sign up to set email alerts
|

Nursing diagnoses related to skin: operational definitions

Abstract: Objective: to validate the operational definitions of the defining characteristics and risk factors of the three NANDA International (NANDA-I) nursing diagnoses and to revise these diagnoses' definitions. Method: content validation of nursing diagnosis. 146 defining characteristics and risk factors were identified in the literature in Brazilian and international databases. This was followed by content validation of the definitions of these diagnoses (presented by NANDA-I) and of the operational definitions (de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
(5 reference statements)
0
3
0
1
Order By: Relevance
“…Thus, the skin in this condition presents greater fragility, because the elasticity is impaired and causes a decrease in thickness, increasing the risk of injury by pressure and trauma. For interventions, light walking is recommended to stimulate venous return, elevation of the lower limbs, adherence to pharmacological therapy, fluid restriction, skin hydration, and comfort massages [12].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the skin in this condition presents greater fragility, because the elasticity is impaired and causes a decrease in thickness, increasing the risk of injury by pressure and trauma. For interventions, light walking is recommended to stimulate venous return, elevation of the lower limbs, adherence to pharmacological therapy, fluid restriction, skin hydration, and comfort massages [12].…”
Section: Resultsmentioning
confidence: 99%
“…It was identified that 90.88% of the evolutions of ND in the ward and 84.79% in the ICU remained unchanged and, considering that the evolution evaluates the results achieved, it is questionable whether these were actually evaluated in the evolution. 11,17 It can be noticed that the data that the nurse evaluates at the moment of its evolution are not the same ones that it evaluates in the ND. It is seen that these two moments should be part of the same reasoning, which was not evidenced in most of the evolutions considered unreliable in both places: 49.86% in the ICU and 35.04% in the ward.…”
Section: Pain Complaintsmentioning
confidence: 99%
“…With aging and during institutionalization (3) , the elderly are at risk of having impaired skin integrity and it is necessary that nurses do this nursing diagnosis more effectively to implement initiatives that contribute to improve care, which can be expensive at first, but will certainly be less costly compared to those inherent complications triggered by a skin lesion in this population (4)(5) .…”
mentioning
confidence: 99%